ANALYSING THE STUDENTSâ GRAMMATICAL ERROR ON WRITING NARRATIVE TEXT - Janah, Miftahul (JURNAL SMART, 2015)
AbstractÂ This qualitative study described about grammatical error on students narrative writing. The participants were the second semester students of STKIP Muhammadiyah Pringsewu Lampung in academic year 2013/ 2014. In collecting data,this study uses forms with general, emerging questions to permit the participant to generate responses. Then, gathering word (text) from the participants, and collecting information from individual of participants. Data analysis tends to consist of text analysis, to involve developing a description and themes, then interpretation tends to sonsist of stating the larger meaning of the findings. After analysing the students writing, it was found that most of mistakes made by students were: missing subject, missing be in simple predicate, wrong simple predicate missing be, superfluous be, misinformation of passive form, the verb comes after the subject, pronoun form, agreement, and reference.Â Key Word: Grammar,Grammatical Error, Writing Skill, Narrative Text